Efficient Assay and Marker Significance of NAD+ in Human Blood - Balashova, Natalia V.; Zavileyskiy, Lev G.; Artiukhov, Artem V.; Shaposhnikov, Leonid A.; Sidorova, Olga P.; Tishkov, Vladimir I.; Tramonti, Angela; Pometun, Anastasia A.; Bunik, Victoria I. (Frontiers in Medicine, 2022)
Nicotinamide adenine dinucleotide (NAD+) is a biological molecule of systemic importance. Essential role of NAD+ in cellular metabolism relies on the substrate action in various redox reactions and cellular signaling. This work introduces an efficient enzymatic assay of NAD+ content in human blood using recombinant formate dehydrogenase (FDH, EC 1.2.1.2), and demonstrates its diagnostic potential, comparing NAD+ content in the whole blood of control subjects and patients with cardiac or neurological pathologies. In the control group (n=22, 25-70 years old), our quantification of the blood concentration of NAD+ (18 M, minimum 15, max 23) corresponds well to NAD+ quantifications reported in literature. In patients with demyelinating neurological diseases (n=10, 18-55 years old), the NAD+ levels significantly (p<0.0001) decrease (to 14 M, min 13, max 16), compared to the control group. In cardiac patients with the heart failure of stage II and III according to the New York Heart Association (NYHA) functional classification (n=24, 42-83 years old), the blood levels of NAD+ (13 M, min 9, max 18) are lower than those in the control subjects (p<0.0001) or neurological patients (p=0.1). A better discrimination of the cardiac and neurological patients is achieved when the ratios of NAD+ to the blood creatinine levels, mean corpuscular volume or potassium ions are compared. The proposed NAD+ assay provides an easy and robust tool for clinical analyses of an important metabolic indicator in the human blood.